VIEWING THE CONTRIBUTION OF NEGATIVE AND POSITIVE FACTORS IN WORK THAT IMPLICATE THE PERFORMANCE OF BANK EMPLOYEES - Syamsi Mawardi; Endah Finatariani (Inovasi, 2022)
There will always be obstacles at work, and the most common one is work stress. The cause of work stress can occur from small things, such as misperceptions, miscommunication, misbehavior, and so on. However, there are other positive factors that also improve performance, one of which is work rules. Work rules become guidelines in disciplining measurable work behavior, so that work results are in accordance with standards. Based on this background, this study aims to analyze negative and positive factors at work, which have implications for performance. The research is built on a quantitative basis, so the basis for disclosing phenomena is the numbers tested by the regression statistical method. The research subjects were private bank employees in the urban city, South Tangerang. Data is collected primary/directly by distributing questionnaires with a Likert scale. The number of samples used was 60 people with census techniques. The results of the study show that there is a significant difference in the effect of discipline and work stress on performance. As it turns out, negative factors such as stress have a stronger power on decreased performance, compared to positive factors such as discipline. So, it is understandable, that suppressing negative factors such as stress, workload, conflict and so on will further maximize the work potential of employees. Then the company increases other positive work factors.Keywords: Positive-Negative Work Factors, Rules, Stress, Performance, Work Achievement